Logical Facts on the Personality of Zaratkhushtra (ZOROASTR) - Mirsultonovich, Is‟hoqov Mirsodiq (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to one of the problems of world avestology related to the personality of Zarathushtra, the founder of the philosophical and religious doctrine of Mazda Yasna (worship of Mazda, that is, the Highest Reason). In the scientific tradition there are various interpretations of this issue. However, there is still no optimal solution to this issue. Someone, if he dated the time of Zarathushtra’s time, was almost an epoch of the Neolithic, another considers him almost a contemporary with the first kings Achaemenids. There are still scholars who consider Zarathushtra a face not historical but legendary. As for his teachings - the collective creativity of the ministers of religion. At the same time, some researchers no doubt see Zarathushtra as the author of the preaching texts of the Avesta "Gat".